Pepper Fruit Fly Atherigona orientalis (Schiner) (Insecta: Diptera: Muscidae) - Kenneth L. Hibbard; William A. Overholt (EDIS, 2012)
Although it is commonly referred to as the pepper fruit fly or tomato fruit fly, Atherigona orientalis is not a true fruit fly in the family Tephritidae, but rather a member of the Muscidae, the same family to which the common house fly belongs. It is found in most tropical and subtropical areas of the world and is usually considered a secondary pest or “trash fly.” But it can sometimes be a primary pest of certain agricultural crops, most notably plants in the family Solanaceae. This 4-page fact sheet was written by Kenneth L. Hibbard and William A. Overholt, and published by the UF Department of Entomology and Nematology, September 2012.